Management System of Information Technology Studies for the Students of Professional Development Courses - Panova, Natalia A.; Bystritskaya, Elena V.; Burkhanova, Irina Y.; Arifulina, Ramilya U.; Aksyonov, Sergei I.; Ivanova, Svetlana S. (International Review of Management and Marketing, 2016)
The relevance of the present research is explained by the need in such a management system of information technology studies for the students of professional development courses that will allow the teachers to boost the process of students' developing necessary skills and make it in a way that is found comfortable for the latter and takes into consideration their individual characteristics. The research aims at determining peculiarities of management systems of information technology studies for the students of professional development courses, the leading method of the research being the learner centred approach that focuses on the ways of teacher-student cooperation in the learning process. The research encompasses the key components of the information technology studies management as in the case of the Tochka Dostupa system (Transl.: Access point) which now sees the implementation of an information system ‘AIS Nalog-3' (Transl.: Information system Tax-3). The use of the said components of the Tochka Dostupa system helps to form students' professional skills necessary for fulfilment of various professional tasks. The materials can be used not only in the management of information technology studies for the students of professional development courses but also for the university and vocational courses students. Keywords: management of information technology studies, Tochka Dostupa system components, teacher-student cooperation, professional skills. JEL Classifications: A22, I23, Z39